Impact of Government Policies on Entrepreneurial Ecosystems: A Comparative Analysis of Developing and Developed Economies - Sipakoly, Selly (International Journal of Business, Law, and Education, 2024)
This research investigates the impact of government policies on entrepreneurial ecosystems through a comparative analysis of developing and developed economies. The study utilizes a mixed-methods approach, including systematic literature reviews, case studies from various countries, and quantitative data analysis. The systematic review reveals diverse policy strategies employed by governments to stimulate entrepreneurship, while case studies highlight policy effectiveness in sectors such as technology, finance, and innovation. Quantitative data analysis elucidates disparities in entrepreneurship rates, access to finance, and regulatory environments across economies. Findings underscore the importance of context-specific policies, sectoral focus, and regional collaboration in fostering vibrant entrepreneurial ecosystems. The research contributes insights and recommendations for policymakers, stakeholders, and researchers to design adaptive policy frameworks that nurture sustainable entrepreneurship and drive economic growth.